2009
DOI: 10.1590/s1516-89132009000700021
|View full text |Cite
|
Sign up to set email alerts
|

Lab-Scale production of Bacillus atrophaeus' spores by solid state fermentation in fifferent types of bioreactors

Abstract: ABSTRACT

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 18 publications
(8 citation statements)
references
References 24 publications
0
8
0
Order By: Relevance
“…Spores production was conducted in trays [36,40] and packed-bed bioreactors [37,38] using different alternative substrates such as wheat bran, maize meal, rice straw and sugarcane bagasse with both fungal (Beauveria bassiana and Clonostachys roses) and bacterial (Bacillus licheniformis) strains. Sporulation reached better results in packed-bed bioreactor from 0.9 to 3.36 spores g dry matter probably due to forced aeration that is promoted in this type of equipment, which is the advantage of this model.…”
Section: Agriculture Bioproducts Produced In Ssf Bioreactorsmentioning
confidence: 99%
“…Spores production was conducted in trays [36,40] and packed-bed bioreactors [37,38] using different alternative substrates such as wheat bran, maize meal, rice straw and sugarcane bagasse with both fungal (Beauveria bassiana and Clonostachys roses) and bacterial (Bacillus licheniformis) strains. Sporulation reached better results in packed-bed bioreactor from 0.9 to 3.36 spores g dry matter probably due to forced aeration that is promoted in this type of equipment, which is the advantage of this model.…”
Section: Agriculture Bioproducts Produced In Ssf Bioreactorsmentioning
confidence: 99%
“…The strain was obtained from Spordex Biological Indicator Strips (Bacillus atrophaeus nrrl#4418, Steris, USA) and spores were aseptically transferred to modified soy bean casein digest broth. B. atrophaeus is a facultative anaerobic, gram-positive and rod that makes endospores (Sella et al 2009). After activation in liquid culture medium, the strain was cultivated in Trypticase Soy Broth.…”
Section: Microorganisms and Culture Mediamentioning
confidence: 99%
“…The research, as reported by Frómeta et al (2020), stated that the pectin content in the coffee pulp increased by 20.5% after being treated with AIS. Another critical factor to consider in the SSF process is the sufficient water content in the medium (Sella et al, 2009). The results proved that the optimum pectinase activity of ISH16 was 0.166 U/ml when SSF was done at 90% water content in the substrate (Figure 2).…”
Section: Optimum Pectinase Productionmentioning
confidence: 88%